The Effect of Chronic Ozone Exposure on the Activation of Endoplasmic Reticulum Stress and Apoptosis in Rat Hippocampus - Rodríguez-Martínez, Erika; Nava-Ruiz, Concepcion; Escamilla-Chimal, Elsa; Borgonio-Perez, Gabino; Rivas-Arancibia, Selva (Frontiers in Aging Neuroscience, 2016)
The chronic exposure to low doses of ozone, like in environmental pollution, leads to a state of oxidative stress, which has been proposed to contribute to neurodegenerative disorders, including Alzheimer's disease. It induces an increase of calcium in the endoplasmic reticulum (ER), which produces ER stress. On the other hand, different studies show that, in diseases such as Alzheimer’s, there exist disturbances in protein folding where ER plays an important role. The objective of this study was to evaluate the state of chronic oxidative stress on ER stress and its relationship with apoptotic death in the hippocampus of rats exposed to low doses of ozone. We used 108 male Wistar rats randomly divided into five groups. The groups received one of the following treatments: 1) Control (air), 2) Ozone (O3) 7 days, 3) O3 15 days, 4) O3 30 days, 5) O3 60 days, and 6) O3 90 days. Two hours after each treatment, the animals were sacrificed and the hippocampus was extracted. Afterwards, the tissue was processed for western blot and immunohistochemistry using the following antibodies: ATF6, GRP8 and caspase 12. It was also performed TUNEL assay and electronic microscopy. Our results show an increase in ATF6, GRP78 and caspase 12 as well as ER ultrastructural alterations and an increase of TUNEL positive cells after 60 and 90 days of exposure to ozone. With the obtained results, we can conclude that oxidative stress induced by chronic exposure to low doses of ozone leads to ER stress. ER stress activates ATF6 inducing the increase of GRP78 in the cytoplasm, which leads to the increase in the nuclear translocation of ATF6. Finally, the translocation creates a vicious cycle that, together with the activation of the cascade for apoptotic cell death, contributes to the maintenance of ER stress. These events potentially contribute in the neurodegeneration processes in diseases like Alzheimer’s Disease.